A shared N-terminal hydrophobic tail for the formation of nanoparticulates. (September 2016) - Zhang, Xiao; Wang, Kaihang; Lin, Qingshan; Zheng, Minghua; Li, Qiong; Li, Tingting; Hong, Qiyang; Zheng, Qingbing; Yu, Hai; Gu, Ying; Li, Shaowei; Xia, Ningshao
Aim: Nanoparticulate design is important for the production of nanotechnological materials and passive immunogens. Using lessons from our hepatitis E vaccine, we herein design protein-based nanoparticles through incorporation of an N-terminal hydrophobic tail (NHT, located on HEV ORF2 aa368–460).Materials & methods: Flu HA1, HIV gp41/gp120/p24, HBsAg and HPV16 L2 were fused with NHT, expressed in Escherichia coli and subjected to self-assembly in vitro . Nanosized particles were characterized by size-exclusion chromatography and negative electron microscopy. Immunogenicity was assessed in mice.Results: All the NHT-fused proteins spontaneously formed nanoparticulates and presented with immunogenicity approximately 2-log over their nonassembling forms.Conclusion: Protein self-assembly provides an attractive means to create nanosized particles that bear specific antigens. Our strategy outlines a novel and shared method for the design of immunogenic nanoparticles.